2011
DOI: 10.1109/tase.2010.2089450
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Paint Gun Orientation in Spray Paint Applications—Experimental Results

Abstract: In this paper, we present the experimental results of a new spray paint algorithm presented in previous publications. Both theory and simulations indicate that the proposed method allows a robotic manipulator to paint a given surface using substantially lower joint torques than with conventional approaches. In this paper, we confirm this by implementing the algorithm on an ABB robot and we find that the joint torques needed to follow the trajectory are substantially lower than for the conventional approach.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 4 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…if a is True then 8q q q des = f f f 1 ; 9 else 10q q q des = f f f 2 ; 11 end Algorithm 2: One iteration in the control system. The choice of θ = 20 • is the same as in [27]. Since the function h(x, y) is a constant, the spray surface is flat, and the desired distance between the nozzle and the point of intersection p p p i is 0.3 m. Note that in these experiments, no paint has actually been applied to a surface.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…if a is True then 8q q q des = f f f 1 ; 9 else 10q q q des = f f f 2 ; 11 end Algorithm 2: One iteration in the control system. The choice of θ = 20 • is the same as in [27]. Since the function h(x, y) is a constant, the spray surface is flat, and the desired distance between the nozzle and the point of intersection p p p i is 0.3 m. Note that in these experiments, no paint has actually been applied to a surface.…”
Section: Methodsmentioning
confidence: 99%
“…This is exploited in [20], where the nonlinear orientation constraints are transformed into positive definiteness constraints imposed on certain symmetric matrices to find the desired orientation every time-step. It is shown that this approach allows the end effector to maintain a higher constant velocity throughout the trajectory guaranteeing uniform paint coating and substantially reducing the time needed to paint the object, something that is experimentally validated in [27].…”
Section: Introductionmentioning
confidence: 98%
“…In this process, it is necessary to transform between the spatial coordinate system of the workpiece and the base coordinate system of the robot (also called workpiece calibration). The transformission between the coordinate system of the end effector and the base coordinate system of the robot is also necessary (also called tool calibration) [21][22][23][24].…”
Section: Trajectorymentioning
confidence: 99%
“…Therefore, it is of vital importance to find the new basis functions of Bézier curves. In this section, Bézier curves are evenly combined with exponential mean, and the definition of exponential mean Bézier curves with parameter is put forward [14,15]. The three basic properties of this kind of curves are given, such as the elevation, de Casteljau algorithm, and segmentation theorem which are applied to the method for generating the painting path in complicated surface.…”
Section: Path Planningmentioning
confidence: 99%